(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
The main feature of causing inflammatory infectious diseases is as a result of mechanical injuries, various injuries of animals occur, the contour of the hoof increases, the animal loses its appetite, and animals suffer severe pain during movement.